2016
DOI: 10.1177/0883073816669450
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol as a Potential Treatment for Febrile Infection-Related Epilepsy Syndrome (FIRES) in the Acute and Chronic Phases

Abstract: Febrile infection-related epilepsy syndrome (FIRES) is a devastating epilepsy affecting normal children after a febrile illness. FIRES presents with an acute phase with super-refractory status epilepticus and all patients progress to a chronic phase with persistent refractory epilepsy. The typical outcome is severe encephalopathy or death. The authors present 7 children from 5 centers with FIRES who had not responded to antiepileptic drugs or other therapies who were given cannabadiol (Epidiolex, GW Pharma) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
121
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 20 publications
1
121
0
5
Order By: Relevance
“…In the remaining 8 clinical trials of various study design, 7 studies reported CBD positively (average dosing 23 mg/kg/d) and 1 study was neutral (8 mg/kg/d) . Within the 12 case studies and case series, 9 described positive effects of CBD (average dosing 16 mg/kg/d), 2 were neutral (average dosing 21 mg/kg/d) and 1 study described mixed results (3 mg/kg/d)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining 8 clinical trials of various study design, 7 studies reported CBD positively (average dosing 23 mg/kg/d) and 1 study was neutral (8 mg/kg/d) . Within the 12 case studies and case series, 9 described positive effects of CBD (average dosing 16 mg/kg/d), 2 were neutral (average dosing 21 mg/kg/d) and 1 study described mixed results (3 mg/kg/d)…”
Section: Resultsmentioning
confidence: 99%
“…Within the other 3 clinical trials of prospective open‐label design ( n = 203), CBD was administered at an average dosing of 42 mg/kg/d and significant improvements in quality of life and seizure frequency compared to baseline were observed . 3 case series and 1 case report (total n = 16) reported beneficial effects of CBD on seizure frequency, duration and severity with an average administered dose of 21 mg/kg/d …”
Section: Resultsmentioning
confidence: 99%
“…2,4,8 Although all our patients developed SRSE over a few days, the initial seizure burden was relatively low. Development of an early biomarker for identification of FIRES is needed, as patients present with relatively nonspecific symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…The diagnosis is one of exclusion made after the infectious, metabolic, genetic, and autoimmune evaluation yields negative results. 2,8,9 Outcomes in children with FIRES are poor, with 10-30% of cases resulting in death, refractory epilepsy in 90% of survivors, and severe intellectual disability in a third. 2,[5][6][7] Most centers trial a combination of antiepileptic and immune-modulating therapies with disappointing results.…”
mentioning
confidence: 99%
See 1 more Smart Citation